Effect of water content on microstructure and properties of magnesium potassium phosphate cement pastes with different magnesia‐to‐phosphate ratios. Issue 6 (22nd February 2021) - Qin, Jihui; Qian, Jueshi; Dai, Xiaobing; You, Chao; Ma, Hongyan; Li, Zhen
Abstract: Magnesium potassium phosphate cement (MKPC) is a class of chemically bonded ceramic for special engineering applications. The selection of mass ratios of MgO‐to‐KH2 PO4 ( M / P ) and water‐to‐cement ( W / C ) is an important aspect for formulating MKPC paste. This paper analyzed the stoichiometry of the primary reaction of MKPC and investigated the effect of W / C (0.14–0.40) on paste microstructure and properties at different M / P (1.5–4). At high M / P, low W / C was sufficient to complete the hydration of KH2 PO4 and higher W / C yielded looser microstructure, dictating that properties of high M / P pastes were monotonic functions of W / C . However, a clear W / C threshold effect was found in medium M / P pastes at both micro‐ and macro‐levels. Low W / C below stoichiometric value suppressed the formation of K‐struvite and favored the presence of an amorphous phase, leading to intense early shrinkage, low early compressive strength, and poor long‐term water resistance. The increase in W / C above stoichiometric value resulted in the segregation of excess water and thus to porous structure, with detrimental effects on dimensional stability and strength. The micro–macro analysis highlighted the importance of stoichiometric water amount in the optimal design of MKPC.